2015
DOI: 10.1016/j.rbmo.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre phase 3 study comparing efficacy and safety of Bemfola® versus Gonal-f® in women undergoing ovarian stimulation for IVF

Abstract: Bemfola (follitropin alfa) (Finox AG, Switzerland), a new recombinant FSH, has a comparable pharmacological profile to that of Gonal-f (Merck Serono, Germany), the current standard for ovarian stimulation. A randomized, multi-centre, Phase 3 study in women undergoing IVF or intracytoplasmic sperm injection (n = 372) showed Bemfola yielding similar efficacy and safety profiles to Gonal-f. Women aged 20-38 years of age were randomized 2:1 to receive a single, daily, subcutaneous 150 IU dose of either Bemfola or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 19 publications
10
75
1
1
Order By: Relevance
“…No difference in severe OHSS was observed between treatment groups (Bemfola: 0.8 %; Gonal-f: 0.8 %). This study demonstrated similar clinical efficacy and safety profiles between Bemfola and Gonal-F, and suggests that Biosimilars can be an appropriate alternative in ovarian stimulation protocols [8].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…No difference in severe OHSS was observed between treatment groups (Bemfola: 0.8 %; Gonal-f: 0.8 %). This study demonstrated similar clinical efficacy and safety profiles between Bemfola and Gonal-F, and suggests that Biosimilars can be an appropriate alternative in ovarian stimulation protocols [8].…”
Section: Discussionsupporting
confidence: 53%
“…The LH hypothesis changed worldwide thinking and the direction of stimulation protocols in ART. ''Pure'' FSH preparations with reduced LH content such as Purified FSH (PoFSH) [5], Highly Purified FSH (PoFSH-HP) [6], Recombinant FSH (recFSH) [7], and Biosimilar recFSH [8] were introduced over the last three decades into clinical practice. There was no consensus reached on the superiority of one preparation over the other till date [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical efficacy was demonstrated in an assessor-blinded, randomized, parallel-group, multicenter, phase III study conducted in women undergoing assisted reproduction techniques at 15 centers in six European countries 6. Clinical equivalence of biosimilar follitropin alfa to the originator product was demonstrated in terms of the number of oocytes retrieved during stimulation of multifollicular development in patients undergoing superovulation for assisted reproductive technology (ART) with a between-treatment group difference of 0.27 (95% CI: −1.34 to 1.32).…”
Section: Introductionmentioning
confidence: 99%
“…A margin of plus or minus three oocytes to demonstrate equivalence between two FSH products has been accepted by the European Medicines Agency as it represents an end-point of clinical relevance (European Medicines Agency, 2013;Rettenbacher et al, 2015) and is tighter than that used to register a modified rhFSH with a longer half-life (−3, +5) (Devroey et al, 2009).…”
Section: Sample Sizementioning
confidence: 99%